Mereduksi Perilaku Konsumtif Melalui Konseling Individu Rebt: Studi Kasus Siswa Kelas VIII SMP NU Terpadu Brebes - Mitha Ayu Nazila; Sulistianingsih; Nur Zainah; Anggun Muryadun N; Muhammad Jalaluddin (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2026)
students at SMP NU Terpadu Brebes, this phenomenon is manifested through excessive purchasing habits, an obsession with following peer trends, and an inability to control the usage of daily pocket money. The negative impacts of this behavioral distortion trigger financial wastefulness, impaired self-control, and disrupted learning focus in the classroom. This study aims to analyze the tangible impacts of consumptive behavior and examine the effectiveness of implementing individual counseling services using the Rational Emotive Behavior Therapy (REBT) approach to reduce this behavior. This study employed a qualitative approach with a case study design. The research subjects consisted of students identified with high and moderate levels of consumptive behavior. Data collection techniques were comprehensively conducted through observation, in-depth interviews, and documentation. The data analysis process applied interactive techniques, including data reduction, data display, and conclusion drawing. The research findings indicate that through REBT counseling interventions, students successfully identified and dismantled their irrational beliefs, such as narcissistic ambitions to gain group social recognition. Post-counseling, students demonstrated significantly positive behavioral changes, characterized by enhanced self-control, wiser management of pocket money, and an objective ability to differentiate between essential needs and momentary desires.